Cloning and sequence analysis of bile salt hydrolase (bsh) gene from Bifidobacterium longum - Shuhaimi, M.; Ali, A.M.; Saleh, N.M.; Yazid, A.M. (Springer Science and Business Media LLC, 2001)
A pair of PCR primers for the rapid detection of bile salt hydrolase (bsh) gene from Bifidobacterium longum BB536 has been synthesised and have revealed the bsh gene of approx 970 bp in Bifidobacterium longum BB 536 but not in other species of bacteria tested. The bsh gene was cloned and sequenced showing a high similarity to bsh gene previously published. The resulting nucleotide sequence encodes a predicted protein of 317 amino acids, Mw = 35 kDa.